A Note on the Inner-Outer Iterative Method for Solving the Linear Equation Ax = b - Li-Tao Zhang; Xian-Yu Zuo; Tong-Xiang Gu; Yan-Ping Wang; Yi-Fan Zhang; Jian-Lei Li; Sheng-Kun Li (Journal of Mathematics, 2020)
Recently, Tian et al. [Computers and Mathematics with Applications, 75(2018): 2710-2722] came up with the inner-outer iterative method to solve the linear equation Ax=b and studied the corresponding convergence of the method. In this paper, we improve the main results of the inner-outer method and get weaker convergence results. Moreover, the parameters can be adjusted suitably so that the convergence property of the method can be substantially improved.